Intelligent optimisation of deep drawing process parameters in the production of aluminium non-rotational symmetric monolithic components - Sarema, Blessed (Stellenbosch : Stellenbosch University, 2025)
Sarema, B. 2025. Intelligent optimisation of deep drawing process parameters in the production of aluminium non-rotational symmetric monolithic components. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/fe12875c-4550-41b2-a3c7-65125f0a644f